Interactive tools, engaged minds: The impact of ClassPoint and EdCafe on learning strategies - Saleh, Shoeb; Mohamed, Tarik N. (Research Journal in Advanced Humanities, 2025)
Student engagement is a critical factor in academic success and enriching learning experiences in higher education. This study explores the impact of two interactive educational AI tools—ClassPoint and EdCafe—on enhancing engagement, participation, and content retention in a GS Psychology course. Using a quasi-experimental design, the study involved 70 undergraduate students. Participants were divided into control and experimental groups. The experimental group utilized ClassPoint (interactive quizzes and annotations) and EdCafe (interactive assignments and class activities), while the control group followed traditional instructional methods. Engagement surveys were the primary data collection method pre and post the intervention for both groups. Findings revealed that the experimental group exhibited significantly higher emotional, cognitive, and behavioral engagement, as well as better test performance, compared to the control group. Students in the experimental group also reported greater enjoyment, motivation, and responsiveness to interactive tasks. These results suggest that incorporating technology-based tools like ClassPoint and EdCafe enhances academic performance and fosters positive student attitudes toward learning. The integration of such platforms creates dynamic and engaging learning environments, promoting deeper comprehension and stronger content retention.